Public perception on the implementation of building and common property (ACT 663) towards DBKL low cost flat / Yang Muhammad Rosyaufi Haji Abdul Latif - Haji Abdul Latif, Yang Muhammad Rosyaufi (Faculty of Architecture, Planning and Surveying, 2014)
Building and Common Property (Act 663) 2007 was being gazetted on the 12th April 2007 which in order to provide a guideline and standard for a proper maintenance and management of property with its common property including for any incidental thereto. Before this act was being implemented, all the maintenance and management of building housing which is two or more storeys and the common property was authorized by the Housing Development ( Control and License) (Act 118) 1966 together with Strata Title 1985 (Act 318),This act have an objective on how to form up a Joint Management Body (JMB) to a particular property for providing the services upon the building and common property of strata building after the delivery of vacant possession (VP) and before the formation of Management Corporation (MC). This act is a legal law that is implemented to all of residential building and if it not being executed based on the law, an offensive law enforcement action will be taken. However, there is a lot of Joint Management Body (JMB) or management parties that should execute the clauses in the act did not take it seriously due to unreasonable factors.